2019
DOI: 10.1097/wno.0000000000000760
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Varying Intranasal Treatment Regimens in ST266-Mediated Retinal Ganglion Cell Neuroprotection

Abstract: Introduction: Prior studies showed that intranasally administered ST266, a novel biological secretome of Amnion-derived Multipotent Progenitor cells containing multiple growth factors and anti-inflammatory cytokines, attenuated visual dysfunction and prevented retinal ganglion cell (RGC) loss in experimental optic neuritis. Long-term effects and dose escalation studies examined here have not been reported previously. Methods: Optic neuritis was induced in the multiple sclerosis model experimental autoimmune en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 48 publications
2
23
1
Order By: Relevance
“…This outcome might also be due to the nature of the MOG 35-55 EAE model, in which several studies aimed at RGC neuroprotection have indicated a huge variability in RGC survival from no to almost complete preservation. [40][41][42] An important factor on RGC survival in EAE models may be the timing of intervention and response of dosages, as nicely demonstrated by Wilmes et al 41 The group of Shindler et al reported a strong correlation on the magnitude RGC survival and the timepoint of corticosteroid intervention in the PLP-induced EAE model. 43 We used a single injection of MSC seven days after EAE induction and taking the half-life of MSC into consideration, a single MSC injection rather than multiple administrations might limit longer lasting neuroprotection as indicated by Payne et al 44 On the other hand, we see a robust rescue effect of the PERG amplitude, preservation of the RNFL, and notable mitigation of RGC loss, which is indicative of a sustained effect on the visual system.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This outcome might also be due to the nature of the MOG 35-55 EAE model, in which several studies aimed at RGC neuroprotection have indicated a huge variability in RGC survival from no to almost complete preservation. [40][41][42] An important factor on RGC survival in EAE models may be the timing of intervention and response of dosages, as nicely demonstrated by Wilmes et al 41 The group of Shindler et al reported a strong correlation on the magnitude RGC survival and the timepoint of corticosteroid intervention in the PLP-induced EAE model. 43 We used a single injection of MSC seven days after EAE induction and taking the half-life of MSC into consideration, a single MSC injection rather than multiple administrations might limit longer lasting neuroprotection as indicated by Payne et al 44 On the other hand, we see a robust rescue effect of the PERG amplitude, preservation of the RNFL, and notable mitigation of RGC loss, which is indicative of a sustained effect on the visual system.…”
Section: Discussionmentioning
confidence: 95%
“…This outcome might also be due to the nature of the MOG 35–55 EAE model, in which several studies aimed at RGC neuroprotection have indicated a huge variability in RGC survival from no to almost complete preservation. 40 42 An important factor on RGC survival in EAE models may be the timing of intervention and response of dosages, as nicely demonstrated by Wilmes et al . 41 The group of Shindler et al .…”
Section: Discussionmentioning
confidence: 98%
“…Intranasal administration of the secretome from multipotent stem/progenitor cells has been proposed as a strategy for treating other diseases, such as retinal ganglion cell loss [ 75 , 76 ], multiple sclerosis [ 77 ], Alzheimer’s disease [ 78 ], and Parkinson’s disease [ 79 ], including recently, alcohol and nicotine consumption [ 58 ]. In all these models, MSC-S has shown anti-inflammatory and antioxidant effects, also improving neurodevelopment and memory function.…”
Section: Discussionmentioning
confidence: 99%
“…Since EAE is the most commonly used animal model for MS with a predominant inflammatory component, it is regularly used to test the effects of new anti-inflammatory treatment strategies and to better understand the pathophysiological mechanisms of on-and off-label drugs. Recent structural and functional measurements such as OCT, VEP, optomotor response, optokinetic response, and electroretinogram (ERG), thereby allow a sensitive longitudinal evaluation of structure and function [79,82,96,106,113,114,[122][123][124][125][126] . Advantages and disadvantages of these in vivo readouts, which are increasingly being used in animal models, are described in Table 2.…”
Section: Testing Anti-inflammatory Strategiesmentioning
confidence: 99%